Pivotal role of High-Mobility Group Box 2 in ovarian folliculogenesis and fertility - Shinichiro Shirouzu; Naohiro Sugita; Narantsog Choijookhuu; Yu Yamaguma; Kanako Takeguchi; Takumi Ishizuka; Mio Tanaka; Fidya Fidya; Kengo Kai; Etsuo Chosa; Yoshihiro Yamashita; Chihiro Koshimoto; et al. (BMC, 2022)
Abstract Background High-Mobility Group Box 1 (HMGB1) and HMGB2 are chromatin-associated proteins that belong to the HMG protein family, and are involved in the regulation of DNA transcription during cell differentiation, proliferation and regeneration in various tissues. However, the role of HMGB2 in ovarian folliculogenesis is largely unknown. Methods We investigated the functional role of HMGB1 and HMGB2 in ovarian folliculogenesis and fertilization using C57BL/6 wild type (WT) and HMGB2-knockout (KO) mice. Ovarian tissues were obtained from WT and HMGB2-KO mice at postnatal days 0, 3, 7, and 2, 6 months of age, then performed immunohistochemistry, qPCR and Western blotting analyses. Oocyte fertilization capability was examined by natural breeding and in vitro fertilization experiments. Results In HMGB2-KO mice, ovary weight was decreased due to reduced numbers of oocytes and follicles. Natural breeding and in vitro fertilization results indicated that HMGB2-KO mice are subfertile, but not sterile. Immunohistochemistry showed that oocytes expressed HMGB2, but not HMGB1, in neonatal and adult WT ovaries. Interestingly, in HMGB2-KO ovaries, a compensatory increase in HMGB1 was found in oocyte nuclei of neonatal and 2-month-old mice; however, this was lost at 6 months of age. Conclusions The depletion of HMGB2 led to alterations in ovarian morphology and function, suggesting that HMGB2 plays an essential role in ovarian development, folliculogenesis and fertilization.